Efl Learners’ Perceptions Of The Impact Of Cultural Knowledge Background On Listening Comprehension. The Case Of Lci Private School Learners In El-eulma –sétif - Lyna, Keraghel; Charif, Ben Boulaid (جامعة الوادي - University of Eloued, 2021)
Abstract Culture-language relationship has led to numerous debates on its role in English skills learning proficiency, particularly listening comprehension skills in different non-native speaking countries. The present study aims to explore Algerian EFL learners’ perceptions of the impact of cultural background knowledge of the target language on their listening comprehension. To achieve this purpose, twenty English language learners, females, and males, from the intermediate level class at the private school of languages (LCI) in El-Eulma, Sétif are selected using purposive sampling. Data is collected through a Likert scale questionnaire webbed to the sample and then analyzed by using SPSS. Participants are given 21 statements based on the agreement Likert scale option on the impact of cultural knowledge on their listening comprehension abilities. The findings reveal that the majority of learners consider having a weak grammar, vague pronunciation, and lack of practice as the cause for having difficulty in understanding the listening material. However, a significant number of learners find it difficult to get the meaning of the listening material when they don’t have the cultural awareness of the topic no matter how easy is the language.
مقال
Keywords: EFL learners ; perceptions ; listening comprehension ; cultural knowledge